Truancy - Reid, Ken (Taylor & Francis, 2002)
Truancy: Short and Long-term Solutions is a practical and accessible guide to dealing with the problem of truancy and non-attendance. It is the first book on the issue to actively focus on solutions to the problem, rather than the causes. Full of practical examples of the latest ways in which schools, teachers, education welfare officers and LEAs try to overcome their attendance difficulties. Ken Reid identifies nearly 120 short-term solutions as well as several long-term strategic approaches. The book also considers parental-condoned absenteeism, alternative curriculum schemes and mentoring, while the final chapter presents some strategic issues which policy-makers and politicians need to overcome. This book provides all teachers, deputy heads, head teachers, education welfare staff, social workers, learning mentors and other caring professionals with a repository of up-to-date ideas and solutions. It is essential reading for anyone involved in addressing the challenge of truancy.